2020
DOI: 10.1101/2020.07.22.214221
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increasing cell-free gene expression yields from linear templates inEscherichia coliandVibrio natriegensextracts by using DNA-binding proteins

Abstract: In crude extract-based cell-free protein synthesis (CFPS), DNA templates are transcribed and translated into functional proteins. Although linear expression templates (LETs) are less laborious and expensive to generate, plasmid templates are often desired over PCR-generated LETs due to increased stability and protection against exonucleases present in the extract of the reaction. Here we demonstrate that addition of a dsDNA-binding protein to the CFPS reaction, termed single-chain Cro protein (scCro), achieves… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…This effect is primarily due to the action of exonuclease V ( Yang et al, 1980 ; Bassett and Rawson, 1983 ) (encoded in the RecBCD operon) ( Dillingham and Kowalczykowski, 2008 ) and endonuclease I (encoded by endA), which are the dominant sources of endonuclease activity in E. coli (I. R. Lehman et al, 1962 ). Previous studies have shown an increase in the efficiency of cell-free protein synthesis from PCR products using several approaches, such as supplementing with exonuclease V inhibitors ( Sitaraman et al, 2004 ; Sun et al, 2014 ), using modified nucleotides downstream the PCR reaction ( Hoffmann et al, 2001 ), incorporating competitive DNA strands containing χ-sites ( Marshall et al, 2017 ), adding dsDNA binding proteins ( Zhu et al, 2020 ), depleting exonuclease V in the crude extracts ( Seki et al, 2008 ), deleting RecBCD with the lambda phage red recombinase ( Michel-Reydellet et al, 2005 ), and generating strains lacking endA ( Michel-Reydellet et al, 2005 ; Hong et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…This effect is primarily due to the action of exonuclease V ( Yang et al, 1980 ; Bassett and Rawson, 1983 ) (encoded in the RecBCD operon) ( Dillingham and Kowalczykowski, 2008 ) and endonuclease I (encoded by endA), which are the dominant sources of endonuclease activity in E. coli (I. R. Lehman et al, 1962 ). Previous studies have shown an increase in the efficiency of cell-free protein synthesis from PCR products using several approaches, such as supplementing with exonuclease V inhibitors ( Sitaraman et al, 2004 ; Sun et al, 2014 ), using modified nucleotides downstream the PCR reaction ( Hoffmann et al, 2001 ), incorporating competitive DNA strands containing χ-sites ( Marshall et al, 2017 ), adding dsDNA binding proteins ( Zhu et al, 2020 ), depleting exonuclease V in the crude extracts ( Seki et al, 2008 ), deleting RecBCD with the lambda phage red recombinase ( Michel-Reydellet et al, 2005 ), and generating strains lacking endA ( Michel-Reydellet et al, 2005 ; Hong et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Terminal protection of the linear DNA can also be achieved by chemically modifying the DNA ends. DNA methylation (Zhu et al, 2020) and terminal phosphorothioates (Sun et al, 2013) were shown to improve expression by 32% and 36% (McSweeney and Styczynski 2021), respectively. We hypothesized that other chemical modifications known for protecting against exonucleases degradation could further increase the yield in our RecBCD-deleted system.…”
Section: Resultsmentioning
confidence: 99%
“…These include using the λ-phage GamS protein (Sitaraman et al 2004) or DNA containing Chi sites (Marshall et al 2017) to inhibit the RecBCD exonuclease complex. Protecting the linear DNA ends by DNA binding proteins has also been successful (Yim et al 2020; Norouzi, Panfilov, and Pardee 2021; Zhu et al 2020), as has the chemical modification of linear DNA ends (McSweeney and Styczynski 2021). All these methods still require supplementation of the extract with additional time- and cost-intensive components or modification of the template to achieve expression from linear DNA.…”
Section: Introductionmentioning
confidence: 99%
“…One easy-to-implement option is the use of biotinylated primers during PCR and later addition of streptavidin to the protein expression reaction to block exonucleases attacking the template from the ends. The same concept had been recently used when adding a DNA-binding protein to linear templates having matching binding sites at the ends ( Zhu et al, 2020a ). This approach had shown good template protection when working with an E. coli CFPS system, though it is less effective than circularizing the PCR product.…”
Section: Expression Templatesmentioning
confidence: 99%